Effect of intraduodenal magnesium sulphate on pancreas and gallbladder of man. Issue 6 (June 1976) - Saunders, J H; Thjodleifsson, B; Wormsley, K G
Abstract : Magnesium sulphate has previously been used as a purgative in a test involving the measurement of the faecal excretion of pancreatic enzymes. In order to validate the use of magnesium sulphate for this purpose, in 18 individuals the pancreatic and biliary response to intravenous infusion of secretin (1 CU/kg-h) plus CCK(1IU/kg-h) were compared with the responses to one of three dose-rates of magnesium sulphate infused into the duodenum. The effect of magnesium sulhphate was also studied during the coincident intravenous administration of the hormones. Intraduodenal magnesium sulphate did not stimulate the secretion of bicarbonate into the duodenum but did evoke the secretion of pancreatic enzymes and discharge of bile. The pancreatic response to the exogenous hormones was not altered by coincident intraduodenal infusion of magnesium sulphate. We conclude that magnesium sulphate is a satisfactory purgative for speeding the intestinal transit of pancreatic enzymes.